Antimicrobial properties and dental pulp stem cell cytotoxicity using carboxymethyl cellulose-silver nanoparticles deposited on titanium plates. Issue 1 (1st January 2016) - Laredo-Naranjo, Martha Alicia; Carrillo-Gonzalez, Roberto; De La Garza-Ramos, Myriam Angelica; Garza-Navarro, Marco Antonio; Torre-Martinez, Hilda H. H.; Del Angel-Mosqueda, Casiano; Mercado-Hernandez, Roberto; Carrillo-Fuentevilla, Roberto
Abstract: Objective: To evaluate the antimicrobial properties and dental pulp stem cells (DPSCs) cytotoxicity of synthesized carboxymethyl cellulose-silver nanoparticles impregnated on titanium plates.Material and methods: The antibacterial effect of silver nanoparticles in a carboxymethyl cellulose matrix impregnated on titanium plates (Ti-AgNPs) in three concentrations: 16%, 50% and 100% was determined by adding these to bacterial cultures of Streptococcus mutans and Porphyromonas gingivalis . The Ti-AgNPs cytotoxicity on DPSCs was determined using a fluorimetric cytotoxicity assay with 0.12% chlorhexidine as a positive control.Results: Silver nanoparticles in all concentrations were antimicrobial, with concentrations of 50% and 100% being more cytotoxic with 4% cell viability. Silver nanoparticles 16% had a cell viability of 95%, being less cytotoxic than 0.12% chlorhexidine.Conclusions: Silver nanoparticles are a promising structure because of their antimicrobial properties. These have high cell viability at a concentration of 16%, and are less toxic than chlorhexidine.